The Use of The Drill Method to Improve Learning Outcomes Ability to Wear A Button Shirt on students with Intellectual Disabilities - Ida Yohaidah (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study was to obtain an overview of the use of the drill method to improve the ability of learning outcomes to wear button-down shirts in students with intellectual disabilities children. The method used in this research is Classroom Action Research (CAR) using the drill method. The subjects in this study were four students of class VII at Sekolah Luar Biasa Asih C Manunggal Bandung Indonesia. The results showed that the use of the drill method can improve the ability of learning outcomes to wear button-down shirts in intellectual disabilities children, this happens because the method used is the drill method. This assessment has an impact on students' abilities based on the results of quantitative data calculations, there is an increase in the ability to wear button-down shirts, the use of the drill method can be applied to improve the ability to wear button-down shirts in students with intellectual disabilities, which can be used by teachers in the learning process.